1996
DOI: 10.1111/j.1365-2982.1996.tb00264.x
|View full text |Cite
|
Sign up to set email alerts
|

Difficulty in estimating localized bowel contraction by colonic manometry: a simultaneous recording of intraluminal pressure and luminal calibre

Abstract: To examine whether or not intraluminal pressure changes at a site in the human colon reflect with fidelity the local bowel wall contractions or relaxation, endoscopic recording of the changes in colonic calibre as a parameter of the motor events with simultaneous manometry was performed at a fixed site in a prepared sigmoid colon during the interdigestive state. In four of the 12 subjects, a total of 20 phasic pressure waves with an amplitude of 13-22 mmHg and a duration of 13-18 sec were obtained in a 20 min … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 9 publications
(1 reference statement)
1
12
0
Order By: Relevance
“…1,2,6,[11][12][13] Elongation of the balloon or bag within the lumen is a major source of error in pressure-volume based distention studies, 1,6,12 and pressure-volume based studies do not allow the detection of short segment contractions and relaxations. Rectal impedance planimetry is not affected by these limitations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2,6,[11][12][13] Elongation of the balloon or bag within the lumen is a major source of error in pressure-volume based distention studies, 1,6,12 and pressure-volume based studies do not allow the detection of short segment contractions and relaxations. Rectal impedance planimetry is not affected by these limitations.…”
Section: Discussionmentioning
confidence: 99%
“…RESULTS: A number of rectoanal motility patterns were observed. A total of 25 episodes with very localized cyclic rectal contractions detected at only one of five channels were observed lasting two to four minutes with a median frequency of three per minute (range, [2][3][4][5][6]. A total of 44 episodes of cyclic rectal contractions propagating over two or more channels were detected lasting 2 to 36 minutes.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Whether solid-state manometry provides a more reliable recording is controversial. In vitro studies showed that the water-perfused system can be unreliable when a perfusion rate of Ͻ0.2 ml/min is used compared with a solid-state system, particularly in the presence of viscous luminal contents (57). This observation is important because previous prolonged studies used perfusion rates of Ͻ0.2 ml/min (1,4,12,24,39).…”
Section: G635mentioning
confidence: 99%
“…Studies with manometers have discussed increasing pressure by contractility of the intestines, but endoscopic research has shown that the pressure increases when the lumen expands. 4 Namely, it is possible that HAPC is not only a continuous conduction of smooth muscle contraction, but is also a flow dynamic pressure transfer phenomenon. It is also known that amplitude of antegrade propagating pressure decreases in the ascending colon and increases from the descending colon to the sigmoid colon, 5 and net hourly forward progress was greater in the left than right colon.…”
Section: Introductionmentioning
confidence: 99%